Metallic Graphene Nanoribbons - Sheng-Yi Xie; Xian-Bin Li (Nano-Micro Letters, 2021)
Abstract Isolated graphene nanoribbons (GNRs) usually have energy gaps, which scale with their widths, owing to the lateral quantum confinement effect of GNRs. The absence of metallic GNRs limits their applications in device interconnects or being one-dimensional physics platform to research amazing properties based on metallicity. A recent study published in Science provided a novel method to produce metallic GNRs by inserting a symmetric superlattice into other semiconductive GNRs. This finding will broader the applications of GNRs both in nanoelectronics and fundamental science.